Modelling Of Advanced Iii-V Compound Semiconductor Devices - Rozik, Nik Nor Amirah (Universiti Sains Malaysia, 2017)
Resonant tunneling diode (RTD) is a type of electronic device that has been reviewed regularly by various researchers. The increasing in number of studying about RTD is because of increased demand and the need to resonant tunneling diodes that have the ability to bear the frequency of terahertz. The very high switching speeds frequency of the resonant tunneling diode has enabled the creation of a wide range of applications in the communication system and the imaging system for low-visibility environment. Resonant tunneling diodes using quantum mechanical works to produce a negative differential resistance (NDR). The function of this project is to understand the mechanism that allows RTD operates in quantum mechanical. In addition, the relationship of physical parameters and RTD I-V characteristics were also studied for a better understanding about the properties of RTD. The characteristics of I-V curves are also investigated and the effect of changes in the physical parameters of the RTD to the I-V graph is study in more details. Silvaco simulation software is used to carry out the studies on two model namely XMBE66 and XMBE230 RTD. A simulation tool based on Green function (Non-Equilibrium Green Function, NEGF) which use effective mass approach has been employed in this quantum transport simulation. This simulation model was also run with different layers epitaxial RTD to investigate the effects of the changes on the characteristics IV. Finally, both of the simulation and measured result of I-V graph were compared to get the best fit by varying the epilayer.